Morphological Analysis of Radical Prostatectomy Specimens: Recent Topics Relevant to Prognosis. (January 2013) - Mazzucchelli, R.; Scarpelli, M.; Lopez-Beltran, A.; Cheng, L.; Di Primio, R.; Montironi, R.
The pathology report should include clinically relevant information as well as provide clinically useful information derived from the macroscopic examination and microscopic evaluation of the radical prostatectomy (RP) specimens. The reporting pathologist should pay particular attention to the evaluation of the prognostic factors proven to be of prognostic importance and useful in clinical patient management, including histological type, grade and volume of cancer, the extent of local invasion and stage of cancer as well as the surgical margins status.